Currency Risk Premia in Global Stock Markets - Merritt, Matthew (IMF Working Papers; Working Paper ;, 2006)
Large fundamental imbalances persist in the global economy, with potential exchange rate implications. This paper assesses whether exchange rate risk is priced across G-7 stock markets. Given the multitude of hedging instruments available, theory suggests that stock market investors should not be compensated for currency risk. However, data covering 33 industry portfolios across seven major stock markets suggest that not only is exchange rate risk priced in many markets, but that it is time-varying and sensitive to currency-specific shocks. With stock market investors typically exhibiting "home bias," this suggests that investors are using equity asset proxies to hedge the exchange rate risks to consumption.